Reliability design of battery management system for power battery. (September 2018) - Xu, Guoning; Du, Xiaowei; Li, Zhaojie; Zhang, Xiaojun; Zheng, Minxin; Miao, Ying; Gao, Yang; Liu, Qianshi
Abstract: This paper proposes a distributed battery management system (BMS) to meet the reliability design requirements. The proposed BMS consist of two parts that is the main control module and the sampling module. The reliability and electromagnetic compatibility design of these two modules are presented. In addition, the state of health (SOH) estimation of the two modules is analysed. A reliability test platform is developed and the test results show that the proposed BMS has high reliability. Highlights: The distributed BMS is developed that can realize the state estimation, failure diagnosis, safety management, heat management and balance management of the battery. Practical application and experimental results show that the distributed BMS designed in this paper can meet the reliability requirement. In this paper, the joint estimation method of SOC and SOH based on real-time battery model is studied, and the implementation of the algorithm is discussed to ensure the reliability of the algorithm. The BMS reliability test system realizes the function test, performance evaluation and environmental reliability test method of BMS. It can carry out the whole vehicle simulation, data acquisition, algorithm, fault diagnosis, BMS working temperature cycle and EMC reliability test method for BMS. Each test module can give test results and Record the test process.